Hope Across Socioeconomic Status: Examining Measurement Invariance of the Children’s Hope Scale Across Socioeconomic Status Groups - Lei, Hui; Wang, Zhihang; Peng, Ze; Yuan, Yanyun; Li, Zhihua (Frontiers in Psychology, 2019)
There has been a growing interest in research on hope in recent years. The Children's Hope Scale (CHS) is the most commonly used scale to evaluate goal-related hopeful thinking in children and adolescents. Socioeconomic status (SES) strongly influences an individual's experiences from childhood and throughout adult life. This study aimed to evaluate the measurement invariance of the CHS across SES. The sample consisted of 1934 Chinese youths (50.4% females) with a mean age of 12.96 (SD = 2.686). An overall family SES score was obtained by totaling the Z scores for family monthly income and parents' education level. The results supported the single-factor model as the baseline model across each SES group. Multi-group confirmatory factor analysis revealed that full measurement invariance did not hold. One factor loading and one intercept were non-invariant. There were also significant differences in latent factor means and raw scores of the CHS across the two groups. The CHS had a stronger convergent validation in the higher SES group than lower SES group. The results suggest that researchers and practitioners should exercise caution when comparing differences in hope measured by the CHS between groups with different SES. We provide more robust statistical evidence in terms of SES differences, indicating that children and adolescents from higher SES backgrounds shower greater hopeful thinking compared with those from lower SES backgrounds.